Assessment of contribution of other users to own total whole‐body RF absorption in train environment. Issue 8 (29th October 2015) - Plets, David; Joseph, Wout; Aerts, Sam; Vermeeren, Günter; Varsier, Nadège; Wiart, Joe; Martens, Luc
Abstract : For the first time, the contribution of radio‐frequent radiation originating from other people's devices to total own whole‐body absorption is assessed in a simulation study. Absorption in a train environment due to base station's downlink is compared with absorption due to uplink (UL) of the user's own mobile device and absorption due to the UL of 0, 1, 5, or 15 other nearby active users. In a Global System for Mobile Communications (GSM) macro cell connection scenario, UL of 15 other users can cause up to 19% of total absorption when calling yourself and up to 100% when not calling yourself. In a Universal Mobile Telecommunications System (UMTS) femtocell connection scenario, UL of 15 other users contributes to total absorption of a non‐calling user for no more than 1.5%. For five other users in the train besides the considered person, median total whole‐body Specific Absorption Rate is reduced by a factor of about 400000 when deploying a UMTS femtocell base station instead of relying on the GSM macrocell. Bioelectromagnetics. 36:597–602, 2015. © 2015 Wiley Periodicals, Inc.